2018
DOI: 10.1177/0038026118778174
|View full text |Cite
|
Sign up to set email alerts
|

‘That’s how Muslims are required to view the world’: Race, culture and belief in non-Muslims’ descriptions of Islam and science

Abstract: Islam's positioning in relation to Western ideals of individuality, freedom, women's rights and democracy has been an abiding theme of sociological analysis and cultural criticism, especially since September 11 th 2001. Less attention has been paid, however, to another concept that has been central to the image of Western modernity: science. This article analyzes comments about Islam gathered over the course of 117 interviews and 13 focus groups with non-Muslim members of the public and scientists in the UK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
(41 reference statements)
2
23
0
2
Order By: Relevance
“…Although science and technology studies has long exposed exclusions and inequalities in science on the basis of gender, race, and socioeconomic status (Xie, ), religious identity as a basis for discrimination is rarely considered. Historians of science have begun to recognize race as an important constituent of constructions of science and religion (Keel, ; Livingstone, ), and some sociological work has highlighted this dynamic (Jones, Catto, Kaden, & Elsdon‐Baker, ). Based on interviews with black and Latinx Christians in the United States, Bolger and Ecklund () found that Latinx participants were more concerned than Black participants about science educators negatively impacting children's faith.…”
Section: New Developmentsmentioning
confidence: 99%
“…Although science and technology studies has long exposed exclusions and inequalities in science on the basis of gender, race, and socioeconomic status (Xie, ), religious identity as a basis for discrimination is rarely considered. Historians of science have begun to recognize race as an important constituent of constructions of science and religion (Keel, ; Livingstone, ), and some sociological work has highlighted this dynamic (Jones, Catto, Kaden, & Elsdon‐Baker, ). Based on interviews with black and Latinx Christians in the United States, Bolger and Ecklund () found that Latinx participants were more concerned than Black participants about science educators negatively impacting children's faith.…”
Section: New Developmentsmentioning
confidence: 99%
“…Islamophobia was associated with both identifications, but in the latter case it was especially prominent (we have explored this in depth in Jones et al, 2019).…”
Section: Civilisational Identificationmentioning
confidence: 92%
“…And it’s absolutely terrifying. I’m not sure what’s going to happen.Cliff, UK, nonreligious, publicIslamophobia was associated with both identifications, but in the latter case it was especially prominent (we have explored this in depth in Jones et al., 2019).…”
Section: Four Types Of Science Identificationmentioning
confidence: 94%
“…In fact there are crucial differences between a strict interpretation of Islam's prescriptions and the native European society that broadly accept the rule of human rights and the equality of sexes and genders (Inci, 2006; Mirzo, 2018). In this context Islam's teachings about sexuality, gender relationships (e.g., Arsel, 2018), girl's, and also boys' inexistent rights of self‐determination, not to mention the occasional female genital mutilation, and marked antisemitism are fundamentally incommensurable with a modern Western lifestyle and the rationality of science that effectively contradicts pivotal elements of Muslim identity and constitutes an ethical barrier to interaction with non‐believers (Arsel, 2018; Hopkins & Kahani‐Hopkins, 2004; Jones, Catto, Kaden, & Elsdon‐Baker, 2019; Sarica, 2018; Schiefer & Möllering, 2012).…”
Section: Complementary Incommensurability: Muslim Immigrants and Natimentioning
confidence: 99%